Conductive paste, dry film, internal electrode, and laminated ceramic capacitor
By using a specific combination of organic solvents and phosphate polyester in the conductive paste, the problem of poor fit between the internal electrode layer and the dielectric layer in the laminated ceramic capacitor is solved, and the effect of suppressing sheet corrosion and improving fit is achieved.
Patent Information
- Application Number
- CN202380051530.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-07-06
- Publication Date
- 2025-02-28
AI Technical Summary
In the manufacturing process of laminated ceramic capacitors, the tightness between the internal electrode layer and the dielectric layer is poor, resulting in problems of interlayer peeling and insufficient capacity, especially on thin-film green sheets.
By using a specific combination of organic solvents and phosphate polyester as additives in the conductive paste, the hardness of the dry film is adjusted, thereby inhibiting sheet corrosion and improving the clinging of the dry film to the green sheet.
It effectively suppresses sheet corrosion, improves the clinging of the laminated body, reduces the phenomenon of interlayer peeling, and significantly improves the performance of the laminated ceramic capacitor.
Smart Images

Figure CN119547166A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste, a dry film, an internal electrode and a multilayer ceramic capacitor. Background Art
[0002] As electronic devices such as mobile phones and digital devices become thinner and shorter, multilayer ceramic devices such as multilayer ceramic capacitors (hereinafter referred to as MLCC) as chip components are also expected to be smaller, have higher capacity, and have higher performance. The most effective way to achieve this is to make the internal electrode layer and dielectric layer thinner and multilayer.
[0003] MLCC is generally manufactured as follows. First, in order to form a dielectric layer, a dielectric green sheet (hereinafter also referred to as "green sheet") is formed of dielectric ceramic powder such as barium titanate (BaTiO3) and an organic binder such as polyvinyl butyral. In addition, in order to form an internal electrode layer, a conductive paste is prepared in which a conductive metal powder is dispersed in an organic carrier containing a resin binder. After printing the conductive paste in a predetermined pattern on the surface of the green sheet, drying is performed to remove the organic solvent to form a dry film as an internal electrode. Next, the dry film and the green sheet are heated and pressed together in a state of stacking multiple layers to form a pressed body. The pressed body is cut and the organic binder is removed at a temperature below 500°C in an oxidizing atmosphere or an inactive atmosphere. Thereafter, it is fired at about 1300°C in a reducing atmosphere so that the internal electrode is not oxidized to obtain a fired chip. Next, a paste for external electrodes is applied to the fired chip, and after firing, nickel plating is performed on the external electrodes to complete the MLCC.
[0004] However, the temperature at which dielectric ceramic powder starts sintering is about 1200°C, which is quite different from the temperature at which conductive metal powders such as nickel start sintering / shrinking, so structural defects such as delamination (interlayer peeling) and cracks are easily generated during the above-mentioned firing process. In particular, as miniaturization and high capacity are achieved, the number of stacked layers increases or the thickness of the dielectric layer becomes thinner, and the occurrence of structural defects becomes more significant.
[0005] The conductive paste for the internal electrode layer has conductive metal powder dispersed in an organic vehicle containing a binder resin, and its viscosity is adjusted by an organic solvent. The binder resin constituting the organic vehicle is generally ethyl cellulose, and the organic solvent is generally terpineol.
[0006] However, when a conductive paste using terpineol as an organic solvent is used in combination with a green sheet using a butyral resin as a binder resin, for example, terpineol may remain in the coating film during the printing and drying process, and in this case, the butyral resin, which is often used as a binder resin in the green sheet, may be dissolved. Such a dissolving effect of the internal electrode paste on the organic binder in the green sheet is called "sheet erosion".
[0007] In multilayer ceramic capacitors, "sheet erosion" does not become a practical problem when the green sheet is relatively thick, such as 10 to 20 μm. However, when the green sheet is relatively thin, such as about 5 μm, if sheet erosion occurs, the butyral resin in the green sheet dissolves, causing the green sheet to swell and dissolve, which may cause holes to form in the conductive paste printed portion when the dielectric green sheet is stacked, or interlayer separation (delamination) between the dielectric layer and the internal electrode layer may occur during firing.
[0008] Due to the influence of such sheet corrosion, the withstand voltage and insulation of MLCC are reduced, the target electrostatic capacitance cannot be obtained, or the load life characteristics are deteriorated. Therefore, in order to avoid such sheet corrosion, materials such as organic solvents used in conductive pastes have been studied.
[0009] For example, it has been proposed to use a solvent having low compatibility with butyral resin as an organic solvent used in a conductive paste for internal electrodes (for example, see Patent Document 1). Specifically, Patent Document 1 proposes a conductive paste using dihydroterpineol acetate.
[0010] In addition, conventional conductive pastes are manufactured using, for example, a cellulose resin (e.g., ethyl cellulose) as a binder resin and, for example, terpineol as an organic solvent. However, when such conductive pastes are used to manufacture the above-mentioned crimped body, the adhesion between the internal electrode layer and the dielectric layer is poor, and interlayer delamination sometimes occurs.
[0011] For example, in Patent Document 2, in an internal electrode slurry containing polyvinyl butyral resin, when an anionic surfactant having a carboxyl group (COOH group) is used as an organic additive, the adhesion between the internal electrode layer and the dielectric layer is sometimes reduced. In order to improve the adhesion, an internal electrode slurry containing nickel powder, ceramic powder, ethyl cellulose resin, polyvinyl butyral resin, an organic solvent and anionic surfactant is proposed, and the acetal resin is contained in an amount of not less than 1 mass % and not more than 2.5 mass % relative to the total amount of the slurry.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent No. 2976268
[0015] Patent Document 2: Japanese Patent Application Publication No. 2017-143202 Summary of the invention
[0016] Problems to be solved by the invention
[0017] However, in recent years, with the miniaturization of electronic components, the internal electrode layers and dielectric layers of multilayer ceramic capacitors are being further thinned, and the number of internal electrode layers and dielectric layers stacked is increasing. In the previous technology, sufficient effects could not be obtained, and sometimes there were problems such as insufficient capacity and interlayer peeling between the internal electrode layer and the dielectric layer.
[0018] In view of such circumstances, an object of the present invention is to provide a conductive paste capable of suppressing sheet erosion and improving the adhesion of a laminated body obtained by laminating a dry film and a green sheet, and an internal electrode of a multilayer ceramic capacitor formed using the conductive paste.
[0019] As a result of intensive research, the inventors of the present invention have discovered that by appropriately specifying the types and contents of additives in a conductive paste based on a combination of specific organic solvents, the hardness of a dry film formed by the conductive paste can be controlled, thereby suppressing sheet erosion of a thin film of raw sheets, improving the adhesion between the dry film and the laminate, and suppressing interlayer delamination, thereby completing the present invention.
[0020] Means used to solve problems
[0021] A conductive paste according to one embodiment of the present invention comprises a conductive metal powder, a ceramic powder, a binder resin, an additive and an organic solvent, wherein the organic solvent is composed of a mixed solvent of (A) and (B), (A) is at least one selected from dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, (B) is at least one selected from ethylene glycol monobutyl ether acetate and dipropylene glycol methyl ether acetate, and the additive contains a phosphate polyester in an amount greater than 0 mass % and less than 2.0 mass % relative to the total amount of the conductive paste.
[0022] In addition, preferably, the conductive metal powder is a metal powder selected from one or more of Ni, Pd, Pt, Au, Ag, Cu and their alloys. In addition, it is preferred that the ceramic powder is a conductive paste of barium titanate (BaTiO3) as a perovskite oxide. In addition, preferably, the ceramic powder is a perovskite oxide ferroelectric. In addition, preferably, in the conductive paste for the internal electrode layer of the multilayer ceramic device, the multilayer ceramic device has a dielectric layer and an internal electrode layer formed using a dielectric green sheet, and the dielectric ceramic powder contained in the dielectric green sheet and the ceramic powder contained in the conductive paste are powders of the same composition.
[0023] In addition, preferably, regarding the above-mentioned conductive paste, when the above-mentioned conductive paste is applied to a green sheet containing barium titanate and polyvinyl butyral resin with a wet film thickness of 38 μm and dried at 75° C. for 20 minutes to obtain a dry film, the Vickers hardness measured under the following conditions is 5 Hv or more and 11 Hv or less.
[0024] (Measurement conditions)
[0025] The Vickers hardness of the surface of the dried film was measured using a micro Vickers hardness tester under the condition of a test force of 98 mN.
[0026] In addition, the dry film according to one embodiment of the present invention is formed using a conductive paste.
[0027] Furthermore, the internal electrodes of the multilayer ceramic capacitor according to one embodiment of the present invention are formed using the above-mentioned dry film.
[0028] A multilayer ceramic capacitor according to an embodiment of the present invention includes internal electrodes and a dielectric layer formed using a dielectric green sheet. The thickness of the dielectric green sheet of the multilayer ceramic capacitor is preferably 3 μm or less.
[0029] Effects of the Invention
[0030] The conductive paste of the present invention can suppress sheet erosion and improve the adhesion of the laminate (dried film-green sheet). In addition, the multilayer ceramic capacitor having the internal electrode of the present invention can suppress sheet erosion and greatly suppress the occurrence of problems such as interlayer delamination caused by poor adhesion of the laminate. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 1 and 2 are a perspective view and a cross-sectional view showing a multilayer ceramic capacitor according to an embodiment. DETAILED DESCRIPTION
[0032] [Conductive paste]
[0033] The conductive paste of this embodiment includes conductive metal powder, ceramic powder, binder resin, organic solvent and additives. In the conductive paste, the conductive metal powder and ceramic powder are dispersed in the organic solvent, and can be suitably used for forming the internal electrodes of multilayer ceramic devices such as multilayer ceramic capacitors. In addition, in this specification, the organic solvent includes an organic solvent for a carrier contained in an organic vehicle and an organic solvent for a slurry used to adjust the viscosity of the conductive paste.
[0034] The conductive paste of this embodiment selects an appropriate amount of additives relative to a specific organic solvent. For example, even when the conductive paste is used on a thin film (for example, a thickness of less than 2 μm) raw sheet and a dry film is formed by screen printing, sheet erosion can be suppressed and the adhesion between the dry film and the raw sheet can be improved.
[0035] The conductive paste of this embodiment contains conductive metal powder, ceramic powder, binder resin, additives, organic solvent, etc.
[0036] (1) The organic solvent contains (A) and (B), (A) is at least one selected from dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, and (B) is at least one selected from ethylene glycol monobutyl ether acetate and dipropylene glycol methyl ether acetate,
[0037] (2) The additive contains phosphate polyester.
[0038] Hereinafter, each component will be described in detail.
[0039] 1. Conductive metal powder
[0040] The conductive metal powder is not particularly limited, and one or more metal powders selected from Ni, Pd, Pt, Au, Ag, Cu and alloys thereof can be appropriately selected and used. Among them, nickel (Ni) powder is the best in consideration of conductivity, corrosion resistance, price, etc. In addition, in order to suppress the rapid gas generation caused by the partial thermal decomposition of the binder resin during the debinding process, the Ni powder may also contain S (sulfur) of about several hundred ppm.
[0041] With the miniaturization of MLCC, in order to form a finer and thinner internal electrode layer, from the perspective of improving the smoothness of the dry film and the dry film density, the particle size of the conductive metal powder is preferably 0.05 to 1.0 μm, and more preferably 0.1 to 0.5 μm. If the particle size of the conductive metal powder is less than 0.05 μm, the specific surface area of the particles becomes too large, so the surface activity of the conductive metal powder becomes too high, which not only has an adverse effect on the drying and debonding properties, but also makes it difficult to obtain appropriate viscosity properties, and sometimes creates the hidden danger of deterioration during the long-term storage of the conductive slurry. In addition, if the particle size of the conductive metal powder is greater than 1.0 μm, the film forming property of the slurry coating film is deteriorated when the thin layer is thinned, and the predetermined electrostatic capacitance cannot be obtained, or the smoothness in the dry film becomes insufficient, and the filling of the metal powder becomes insufficient, and the desired dry film density cannot be ensured, so it is difficult to form a sufficiently fine and thin uniform internal electrode, so it is not preferred.
[0042] The content of the conductive metal powder in the conductive paste is preferably 40 to 60% by mass, more preferably 45 to 55% by mass. In addition, the content of the conductive metal powder may be 50% by mass or more. When the content is less than 40% by mass, sufficient conductivity cannot be obtained, and when the content is greater than 60% by mass, the dispersibility may sometimes decrease.
[0043] 2. Ceramic powder
[0044] The ceramic powder is not particularly limited and can be appropriately selected from known ceramic powders according to the type of the applied multilayer ceramic device. As the ceramic powder, it is preferred to use a ferroelectric perovskite oxide, and barium titanate (BaTiO3, hereinafter sometimes referred to as BT) is particularly preferred.
[0045] In addition, the ceramic powder may be a ceramic powder having barium titanate as a main component and containing oxides (e.g., oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb and one or more rare earth elements) as a secondary component. In addition, a ceramic powder of a perovskite-type oxide ferroelectric in which the Ba atoms and Ti atoms of barium titanate (BaTiO3) are replaced with other atoms, Sn, Pb, Zr, etc. may also be used.
[0046] In the case of the conductive paste for the internal electrode of the multilayer ceramic device, the ceramic powder can use the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic device. As the ceramic powder, in addition to the above, for example, oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element)2O3, TiO2, and Nd2O3 can be selected. In addition, the ceramic powder can be used alone or in combination of two or more.
[0047] The conductive paste for the internal electrode layer contains a ceramic powder mainly composed of a perovskite oxide such as a barium titanate system or a strontium zirconate system similar to the composition of the dielectric layer, thereby suppressing the early sintering / shrinkage of the internal electrode layer. As a result, the sintering behavior of the conductive metal powder can be controlled, and the mismatch between the sintering shrinkage behavior of the internal electrode layer and the dielectric layer can be controlled. In addition, it is also possible to suppress the decrease in electrical properties such as the increase in dielectric loss caused by structural defects caused by the fact that the constituent elements of the dielectric ceramic powder as the main component of the dielectric layer are greatly different from the constituent elements of the ceramic powder contained in the conductive paste.
[0048] The particle size of the ceramic powder is preferably in the range of 0.01 μm or more and 0.5 μm or less, and more preferably in the range of 0.01 μm or more and 0.3 μm or less. If the particle size of the ceramic powder is in the above range, a sufficiently fine and thin uniform internal electrode layer can be formed. If the particle size of the ceramic powder is less than 0.01 μm, the specific surface area of the particles becomes too large, so the surface activity of the ceramic powder becomes too high, which not only has an adverse effect on the drying and debonding properties, but also is difficult to obtain appropriate viscosity characteristics, and sometimes there is a hidden danger of deterioration during the long-term storage of the conductive slurry. On the other hand, if the particle size of the ceramic powder is greater than 0.5 μm, the film-forming property of the conductive slurry is deteriorated when the coating film is thinned, and sometimes the predetermined electrostatic capacitance cannot be obtained, and the smoothness in the dry film becomes insufficient. In addition, when the particle size of the ceramic powder is too large, the filling of the ceramic powder becomes insufficient, and the desired dry film density cannot be ensured.
[0049] The particle size of the ceramic powder is a value obtained by observation using a scanning electron microscope (SEM), and is an average value (SEM average particle size) obtained by measuring the particle sizes of a plurality of particles individually from an image observed by SEM at a magnification of 50,000 times.
[0050] The content of the ceramic powder is, for example, 1 mass % to 20 mass % or less, and preferably 3 mass % to 10 mass % or less, relative to the entire conductive paste. When the content of the ceramic powder is within the above range, dispersibility and sinterability are excellent.
[0051] 3. Adhesive resin
[0052] The binder resin is not particularly limited, and a known resin that is soluble in an organic solvent as described later can be used. Examples of the binder resin include cellulose resins such as methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and nitrocellulose, acrylic resins, butyral resins, and the like. Among them, as the binder resin, cellulose resins and butyral resins are preferred, and cellulose resins are more preferred. Examples of butyral resins include polyvinyl butyral. In addition, the cellulose resin is preferably ethyl cellulose. In addition, the molecular weight of the binder resin is preferably about 20,000 to 200,000.
[0053] When the binder resin includes a cellulose resin (eg, ethyl cellulose), the content of the cellulose resin may be 30% by mass or more, 60% by mass or more, 70% by mass or more, or 100% by mass relative to the entire binder resin.
[0054] In addition, for example, it is known that the adhesion strength between the green sheet and the dry film can be improved by including a specific amount of butyral resin as a binder resin (for example, refer to paragraphs
[0005] and
[0024] of Patent Document 2). However, in the conductive paste of the present embodiment, as described later, by including a phosphate polyester as an additive, the adhesion strength between the green sheet and the dry film can be sufficiently improved even when no butyral resin is contained or the content of the butyral resin is low (for example, less than 1% relative to the entire conductive paste).
[0055] When the binder resin includes a butyral resin, the content of the butyral resin can be 70% by mass or less, 40% by mass or less, or 30% by mass or less relative to the entire binder resin. In addition, the lower limit of the butyral resin is not particularly limited, and can be 5% by mass or more, or 10% by mass or more relative to the entire binder resin. When the butyral resin is included in the above range, the adhesion can be further improved.
[0056] The content of the binder resin is preferably 0.5% by mass or more and 10% by mass or less, and more preferably 1% by mass or more and 7% by mass or less, relative to the entire conductive paste. When the content of the binder resin is within the above range, the conductivity and dispersibility are excellent.
[0057] 4. Organic solvents
[0058] The organic solvent may include an organic solvent for an organic vehicle and an organic solvent for adjusting viscosity. For example, the organic solvent as a constituent of the organic vehicle may be used to dissolve a binder resin, or may be used to disperse conductive metal powder, ceramic powder and the organic vehicle, adjust the viscosity of the entire conductive paste, and print the conductive paste in a predetermined pattern.
[0059] In addition, the organic solvent preferably includes (A) and (B), (A) is at least one acetate solvent selected from dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, and (B) is at least one acetate solvent selected from ethylene glycol monobutyl ether acetate and dipropylene glycol methyl ether acetate. When these organic solvents are included, sheet erosion is suppressed, and when used in combination with the phosphate polyester described later, the hardness of the dried film can be adjusted to an appropriate range, thereby improving adhesion.
[0060] As the acetate solvent (A), isobornyl acetate (IBA) is preferably used, and as the acetate solvent (B), ethylene glycol monobutyl ether acetate (EGBA) is preferably used. In addition, the organic solvent is more preferably composed of a mixed solvent formed by mixing the acetate solvent (A) and the acetate solvent (B). When such a mixed solvent is used, the adjustment of the viscosity characteristics of the conductive paste becomes easier, and the drying speed of the conductive paste can be accelerated. In addition, by combining the mixed solvent with a phosphate polyester (additive), the adhesion can be further improved.
[0061] As the organic solvent for viscosity adjustment, the acetate solvent (A) is preferably contained in an amount of 50% by mass or more and 90% by mass or less, more preferably 60% by mass or more and 80% by mass or less, relative to 100% by mass of the organic solvent (for viscosity adjustment). In addition, the acetate solvent (B) is preferably contained in an amount of 10% by mass or more and 50% by mass or less, more preferably 20% by mass or more and 40% by mass or less, relative to 100% by mass of the organic solvent (for viscosity adjustment).
[0062] In addition, the organic solvent is used for adjusting the viscosity of the conductive paste and also for adjusting the organic vehicle. As the organic solvent for adjusting the organic vehicle, it is preferred to use an organic solvent of the same type as the organic solvent for adjusting the viscosity of the conductive paste, such as an acetate-based solvent (A) or an acetate-based solvent (B), because the compatibility with the organic vehicle is improved.
[0063] In addition, as the organic solvent (whole) contained in the conductive paste, the acetate solvent (A) may be contained in an amount of 50% to 90% by mass, or 80% to 90% by mass, relative to 100% by mass of the organic solvent. In addition, the acetate solvent (B) may be contained in an amount of 10% to 50% by mass, or 10% to 20% by mass, relative to 100% by mass of the organic solvent.
[0064] The conductive paste may contain organic solvents other than those mentioned above. Other organic solvents added for the purpose of adjusting the viscosity of the conductive paste are not particularly limited as long as they do not deteriorate the properties of the conductive paste, and generally used organic solvents can be used.
[0065] The total content of the organic solvent contained in the conductive paste can be, for example, 10% by mass or more and 50% by mass or less, and preferably 20% by mass or more and 40% by mass or less, based on the total amount of the conductive paste.
[0066] 5. Additives
[0067] (Phosphate Polyester)
[0068] The conductive paste of this embodiment contains phosphate polyester as an additive. In addition, phosphate polyester refers to a structure of a copolymer (polyester) having a phosphate group and an ester structure. By making the conductive paste contain phosphate polyester in a specific amount, the hardness of the dried film can be adjusted to an appropriate range and the adhesion can be improved.
[0069] The molecular weight of the phosphoric acid polyester is not particularly limited, and is, for example, preferably 250 or more and 3000 or less, more preferably 1000 or more and 3000 or less, and further preferably 1500 or more and 2500 or less. In addition, the acid value of the phosphoric acid polyester is not particularly limited, and may be, for example, 10 mgKOH / g or more and about 300 mgKOH / g or less, 50 mgKOH / g or more and 200 mgKOH / g or less, or 100 mgKOH / g or more and 150 mgKOH / g or less.
[0070] By making the conductive paste contain phosphate polyester, the aggregation of conductive powders can be particularly prevented. In addition, by combining with the above-mentioned specific organic solvent and containing polyphosphate ester, the dried film can have appropriate softness, which can improve the adhesion with the green sheet and prevent interlayer peeling when the press-bonded body is cut into a predetermined chip size.
[0071] The phosphoric acid polyester is contained in an amount of more than 0% by mass and 2.0% by mass or less, preferably 0.05% by mass or more and 1.0% by mass or less, and more preferably 0.1% by mass or more and 0.5% by mass or less, based on the total amount of the conductive paste.
[0072] (Other additives)
[0073] In the conductive paste of this embodiment, various additives other than the phosphate polyester may be further added for the purpose of improving the dispersibility of the conductive powder and the viscosity of the conductive paste. Examples thereof include commercially available additives such as surfactants, chelating agents, dispersants, defoamers, plasticizers, and viscosity modifiers. The timing of adding these additives is not particularly limited, and the printing characteristics of the conductive paste can be adjusted, for example, by adding them to an organic vehicle and kneading them.
[0074] The additive may include, for example, a dispersant. As the dispersant, for example, an acidic dispersant, an alkaline dispersant, a nonionic dispersant, and an amphoteric surfactant may be used. As the acidic dispersant, for example, a carboxylic acid dispersant may be cited, and as the alkaline dispersant, for example, an amine dispersant may be cited. In addition, the conductive paste may not include the above-mentioned dispersant as an additive. For example, the conductive paste of the present embodiment can improve the adhesion even without including a carboxylic acid dispersant. In addition, the above-mentioned dispersant can improve the dispersibility of the conductive powder and ceramic powder in the conductive paste, but does not have the effect of controlling the plasticity of the dry film and improving the adhesion as the phosphate polyester used in the present embodiment, or even if there is, the effect is very low.
[0075] 6. Conductive paste preparation and characteristics
[0076] The conductive paste of this embodiment can be prepared by preparing the above-mentioned components and stirring and kneading them using a mixer. For example, the binder resin can be dissolved in the organic solvent for the carrier in advance to prepare the organic carrier. In addition, when multiple binder resins are used, the organic carrier can be prepared according to the type of binder resin. In addition, the conductive metal powder, ceramic powder, organic carrier and additives can be added to the organic solvent for adjusting the viscosity of the paste, and stirred and kneaded by a mixer to prepare the conductive paste.
[0077] The conductive paste of this embodiment has a Vickers hardness of preferably 5 Hv to 11 Hv, preferably 7 Hv to 10 Hv, and more preferably 7 Hv to 9 Hv, measured under the following conditions. When the Vickers hardness is within the above range, the obtained dry film has moderate softness and can have higher adhesion.
[0078] (Measurement conditions)
[0079] After applying the conductive paste to a wet film thickness of 38 μm on a green sheet containing barium titanate and polyvinyl butyral resin, the film was dried at 75°C for 20 minutes to obtain a dry film. The surface of the obtained dry film was measured at more than 5 points using a micro Vickers hardness tester under a test force of 98 mN, and the average value obtained was taken as the Vickers hardness of the conductive paste (dry film).
[0080] [Multilayer Ceramic Capacitors]
[0081] Hereinafter, an example of an embodiment of a multilayer ceramic capacitor will be described with reference to the accompanying drawings. In the accompanying drawings, the components may be shown schematically or with a changed scale as appropriate. Figure 1 The position and direction of the member are described using an XYZ orthogonal coordinate system shown in FIG. In the XYZ orthogonal coordinate system, the X direction and the Y direction are horizontal directions, and the Z direction is a vertical direction (up and down direction).
[0082] Figure 1 A in and Figure 1 B in FIG. 1 is a diagram showing a multilayer ceramic capacitor 1. The multilayer ceramic capacitor 1 includes a ceramic multilayer body 10 in which dielectric layers 12 and internal electrode layers 11 are alternately stacked, and external electrodes 20.
[0083] The following is a method for manufacturing a multilayer ceramic capacitor using the above-mentioned conductive paste. First, a conductive paste is printed on a ceramic green sheet and dried to form a dry film. After a plurality of green sheets having the dry film on the upper surface are stacked by pressure bonding to obtain a laminate, the laminate is fired and integrated to produce a ceramic laminate 10 in which internal electrode layers 11 and dielectric layers 12 are alternately stacked. Thereafter, a pair of external electrodes 20 are formed at both ends of the ceramic laminate 10 to manufacture a multilayer ceramic capacitor 1. The following is a more detailed description.
[0084] First, a green sheet as an unfired ceramic sheet is prepared. Examples of the green sheet include a dielectric layer slurry obtained by adding a binder resin such as polyvinyl butyral and a solvent such as terpineol to a raw material powder of a predetermined ceramic such as barium titanate, coating the slurry on a support film such as a PET film in a sheet shape, and drying the slurry to remove the solvent.
[0085] In addition, the thickness of the green sheet is not particularly limited. From the perspective of the miniaturization requirement of the multilayer ceramic capacitor, it is, for example, 3 μm or less, 2 μm or less, preferably 0.3 μm or less, and 0.2 μm or less. In addition, the lower limit of the thickness of the green sheet is, for example, 0.05 μm or more. The conductive paste of this embodiment can suppress sheet erosion and improve adhesion even when a thin-film green sheet is used.
[0086] Next, a plurality of sheets are prepared in which a conductive paste is printed and applied on one side of a raw sheet and dried to form a dry film on one side of the raw sheet. In addition, the printing method of the conductive paste is not particularly limited, and a known method such as screen printing or gravure printing can be used, but the conductive paste of this embodiment can preferably be printed using screen printing. In addition, the viscosity of the conductive paste is not particularly limited. In the case of a conductive paste for screen printing, for example, a shear rate of 4s -1 The viscosity at (25°C) may be 10 Pa·s or more. The upper limit of the viscosity of the conductive paste may be, for example, 100 Pa·s or less, or 50 Pa·s or less. In addition, from the perspective of the thinning requirement of the internal electrode layer 11, the thickness of the dry film formed by the conductive paste after drying may be 1.5 μm or less, or 1 μm or less. In addition, the lower limit of the thickness of the dry film is not particularly limited, and is, for example, about 0.5 μm or more.
[0087] In addition, the Vickers hardness of the dry film of the present embodiment is preferably 5Hv or more and 11Hv or less, more preferably 7Hv or more and 10Hv or less, and may be 7Hv or more and 9Hv or less. When the Vickers hardness is in the above range, the dry film has appropriate softness, and the adhesion between the dry film and the green sheet is further improved. In addition, the Vickers hardness is an average value obtained by measuring the Vickers hardness of the dry film surface at more than 5 points under the condition of a test force of 98mN using a micro Vickers hardness meter, as described in the examples described later.
[0088] Next, the green sheet is peeled off from the support film, and the green sheets and the dry films formed on one surface of the green sheets are alternately stacked, and then heated and pressurized to obtain a laminate. In addition, a protective ceramic green sheet not coated with the conductive paste may be further arranged on both sides of the laminate.
[0089] Next, after the laminate is cut into a predetermined size to form a raw chip, the raw chip is subjected to a debinding treatment and fired in a reducing atmosphere, thereby manufacturing a laminated ceramic fired body (ceramic laminate 10). In addition, the atmosphere in the debinding treatment is preferably air or N2 gas atmosphere. The temperature during the debinding treatment is, for example, above 200°C and below 400°C. In addition, it is preferred that the holding time of the above temperature during the debinding treatment is set to be above 0.5 hours and below 24 hours. In addition, in order to suppress the oxidation of the metal used in the internal electrode layer, the firing is carried out in a reducing atmosphere. In addition, the temperature during the firing of the laminate is, for example, above 1000°C and below 1350°C, and the holding time of the temperature during the firing is, for example, above 0.5 hours and below 8 hours.
[0090] By firing the green chip, the organic binder in the ceramic green sheet is completely removed, and the raw material powder of the ceramic is fired to form a ceramic dielectric layer 12. In addition, the organic vehicle in the dry film is removed, and the nickel powder or the alloy powder containing nickel as the main component is sintered or melted to form an internal electrode layer 11, thereby forming a laminated ceramic fired body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. In addition, from the viewpoint of bringing oxygen into the interior of the dielectric layer to improve reliability and suppressing reoxidation of the internal electrode, the laminated ceramic fired body after firing can be subjected to annealing treatment.
[0091] Then, a pair of external electrodes 20 are provided on the manufactured multilayer ceramic fired body to manufacture the multilayer ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. In addition, as a material of the external electrode 20, for example, copper, nickel, or an alloy thereof can be appropriately used. In addition, electronic components other than multilayer ceramic capacitors can also be used.
[0092] Example
[0093] Hereinafter, the present invention will be described in detail based on Examples and Comparative Examples, but the present invention is not limited to these Examples at all.
[0094] [Characteristics of conductive paste]
[0095] The properties of the dried film obtained from the conductive paste were evaluated under the following conditions.
[0096] (1) Sheet erosion
[0097] On the surface of a 2 μm thick green sheet (containing barium titanate (BT) and polyvinyl butyral), a conductive paste was printed in a wet film thickness of 38 μm, and dried at 75°C for 20 minutes to obtain a sheet (a dry film sheet) having a dry film formed on the green sheet. Immediately after the dry film sheet was formed, the back of the dry film sheet was observed under a microscope, and if the swelling phenomenon peculiar to sheet erosion was not confirmed, it was evaluated as ○ (sheet erosion was good), and if the swelling phenomenon was confirmed, it was evaluated as × (sheet erosion was poor).
[0098] (2) Dry film hardness
[0099] On a green sheet (containing barium titanate (BT) and polyvinyl butyral) having a thickness of 4.5 μm, a conductive paste was applied so as to have a wet film thickness of 38 μm, and dried at 75°C for 20 minutes to obtain a dry film sheet. The obtained dry film sheet was subjected to surface Vickers hardness measurement at n=5 points using a micro Vickers hardness tester (HMV-G21DT) manufactured by Shimadzu Corporation under a test force of 98 mN, and the average value was obtained.
[0100] (3) Adhesion
[0101] A conductive paste (sample) was applied to the surface of a pre-made green sheet containing barium titanate and polyvinyl butyral to form a conductive paste film with a wet film thickness of 38 μm. A sheet consisting of the green sheet obtained and the conductive paste film for internal electrodes formed on its surface was dried at 75°C for 20 minutes to obtain a sheet (dried film sheet) having a dry film formed on the green sheet. The dry film sheet and another green sheet were overlapped in such a manner that the green sheet sandwiched the surface coated with the conductive paste (the surface with the dry film formed), and then pressed at a temperature of 40°C and a pressure of 20 MPa for 20 seconds to produce a laminate (for evaluation).
[0102] The obtained laminate was cut into 1 cm squares, and both sides of the laminate were respectively set in the clamps of a tensile tester (AGS-50NX manufactured by Shimadzu Corporation) using tape, and a tensile test was performed. When tension was applied at a test speed of 20 mm / min, the case where interlayer delamination occurred at the interface between the green sheet and the conductive paste dry film was evaluated as "×", and the case where tension could be continuously applied until the tape was peeled without interlayer delamination was evaluated as "0".
[0103] [Materials used]
[0104] (Conductive metal powder)
[0105] Nickel powder (particle size: 0.2 μm) was used as the conductive metal powder.
[0106] (Ceramic powder)
[0107] Barium titanate (BT, particle size: 0.05 μm) was used as the ceramic powder.
[0108] (Organic Carrier)
[0109] As the organic vehicle, organic vehicle 1 and organic vehicle 2 were used.
[0110] The organic vehicle 1 was prepared by mixing ethyl cellulose (EC) as a binder resin and isobornyl acetate as an organic solvent at a predetermined ratio (resin: organic solvent = 20:80, weight ratio), and heating and mixing the mixture at 60°C.
[0111] The organic vehicle 2 was prepared by mixing polyvinyl butyral (PVB) as a binder resin and isobornyl acetate as an organic solvent at a predetermined ratio (resin: organic solvent = 15:85, weight ratio), and heating and mixing the mixture at 60°C.
[0112] In addition, the organic solvents of the organic vehicles 1 and 2 were replaced with terpineol (TPO) to prepare organic vehicles 1' and 2'.
[0113] (Organic Solvent)
[0114] As the organic solvent 1, isobornyl acetate (acetate-based solvent (A)) was used, and as the organic solvent 2, ethylene glycol monobutyl ether acetate (acetate-based solvent (B)) was used.
[0115] (additive)
[0116] As the additive, a phosphoric acid polyester having a molecular weight of 250 or more and 3000 or less is used.
[0117] (Example 1)
[0118] As shown in Table 1, nickel powder (Ni) with a particle size of 0.2 μm as a conductive metal powder: 51.0 mass%, barium titanate (BT) with a particle size of 0.05 μm as a ceramic powder: 7.7 mass%, the above-mentioned organic vehicle 1: 10.1 mass%, organic vehicle 2: 4.3 mass%, and phosphate polyester: 0.1 mass% are dissolved in a mixed solvent of 21.4 mass% of organic solvent 1 and 5.4 mass% of organic solvent 2 to prepare a conductive slurry.
[0119] (Example 2)
[0120] As shown in Table 1, nickel powder (Ni) with a particle size of 0.2 μm as a conductive metal powder: 51.0 mass%, barium titanate (BT) with a particle size of 0.05 μm as a ceramic powder: 7.7 mass%, the above-mentioned organic vehicle 1: 10.1 mass%, organic vehicle 2: 4.3 mass%, and phosphate polyester: 0.3 mass% are dissolved in 21.2 mass% of organic solvent 1 and 5.4 mass% of organic solvent 2 to prepare a conductive paste.
[0121] (Example 3)
[0122] As shown in Table 1, nickel powder (Ni) with a particle size of 0.2 μm as a conductive metal powder: 51.0 mass%, barium titanate (BT) with a particle size of 0.05 μm as a ceramic powder: 7.7 mass%, the above-mentioned organic vehicle 1: 10.1 mass%, organic vehicle 2: 4.3 mass%, and phosphate polyester: 0.5 mass% are dissolved in 21.0 mass% of organic solvent 1 and 5.4 mass% of organic solvent 2 to prepare a conductive paste.
[0123] (Comparative Example 1)
[0124] As shown in Table 1, nickel powder (Ni) with a particle size of 0.2 μm as a conductive metal powder: 51.0 mass%, barium titanate (BT) with a particle size of 0.05 μm as a ceramic powder: 7.7 mass%, the above-mentioned organic vehicle 1: 10.1 mass%, and organic vehicle 2: 4.3 mass% are dissolved in 21.5 mass% of organic solvent 1 and 5.4 mass% of organic solvent 2 to prepare a conductive slurry.
[0125] (Comparative Example 2)
[0126] As shown in Table 1, nickel powder (Ni) with a particle size of 0.2 μm as a conductive metal powder: 51.0 mass%, barium titanate (BT) with a particle size of 0.05 μm as a ceramic powder: 7.7 mass%, the above-mentioned organic vehicle 1': 10.1 mass%, organic vehicle 2': 4.3 mass%, and phosphoric acid polyester: 0.5 mass% were dissolved in 26.4 mass% of terpineol to prepare a conductive paste.
[0127] Table 1 shows the component compositions of Examples 1 to 3 and Comparative Examples 1 and 2, and Table 2 shows the evaluation results.
[0128] Table 1
[0129]
[0130] Table 2
[0131]
[0132] (Evaluation results)
[0133] As can be seen from Tables 1 and 2, in Examples 1 to 3 using the conductive paste of the present embodiment, sheet erosion did not occur, the film hardness was low, and the adhesion was improved.
[0134] On the other hand, it can be seen that in Comparative Example 1 which does not contain phosphoric acid polyester, sheet erosion is not observed, but the film hardness is high and the adhesion is low. In addition, it can be seen that in Comparative Example 2 which uses an organic solvent other than the present embodiment, since phosphoric acid polyester is contained, sheet erosion occurs and the adhesion is reduced although the film hardness is low.
[0135] As described above, the conductive paste of the present embodiment can prevent sheet corrosion and improve adhesion by using a specific organic solvent and containing a specific amount of phosphate polyester, which is significantly improved compared to conventional products.
[0136] Industrial Applicability
[0137] The conductive paste involved in this embodiment can suppress problems such as interlayer delamination caused by poor adhesion of the laminated body in the manufacturing process of the laminated ceramic capacitor using thin-film green sheets, and is particularly suitable for use as a raw material for internal electrodes of laminated ceramic capacitors that are chip components of electronic devices such as mobile phones and digital devices.
[0138] This embodiment includes the following configurations.
[0139] [1] A conductive paste comprising conductive metal powder, ceramic powder, a binder resin, an additive and an organic solvent, wherein:
[0140] The organic solvent comprises (A) and (B), (A) is at least one selected from dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, (B) is at least one selected from ethylene glycol monobutyl ether acetate and dipropylene glycol methyl ether acetate,
[0141] The additive contains more than 0 mass % and 2.0 mass % or less of the phosphoric acid polyester based on the total amount of the conductive paste.
[0142] [2] The conductive paste according to [1] above, wherein the conductive metal powder is composed of a metal powder selected from Ni, Pd, Pt, Au, Ag, Cu and alloys thereof.
[0143] [3] The conductive paste according to [1] or [2] above, wherein the ceramic powder is barium titanate (BaTiO 3 ) which is a perovskite-type oxide.
[0144] [4] The conductive paste according to any one of [1] to [3] above, wherein the ceramic powder is a perovskite-type oxide ferroelectric.
[0145] [5] The conductive paste according to any one of [1] to [4] above, which is a conductive paste for an internal electrode layer of a multilayer ceramic device, wherein the multilayer ceramic device has a dielectric layer and the internal electrode layer formed using a dielectric green sheet, and the dielectric ceramic powder contained in the dielectric green sheet and the ceramic powder contained in the conductive paste have the same composition.
[0146] [6] The conductive paste according to any one of [1] to [5] above, wherein when the conductive paste is applied to a green sheet containing barium titanate and polyvinyl butyral resin to a wet film thickness of 38 μm and dried at 75° C. for 20 minutes to obtain a dry film, the Vickers hardness measured under the following conditions is 5 Hv or more and 11 Hv or less,
[0147] (Measurement conditions)
[0148] The Vickers hardness of the surface of the dried film was measured using a micro Vickers hardness tester under the condition of a test force of 98 mN.
[0149] [7] A dry film formed using the conductive paste according to any one of [1] to [6] above.
[0150] [8] An internal electrode of a multilayer ceramic capacitor, wherein the internal electrode is formed using the dry film according to [7] above.
[0151] [9] A multilayer ceramic capacitor comprising the internal electrode according to [8] above and a dielectric layer formed using a dielectric green sheet.
[0152]
[10] The multilayer ceramic capacitor according to [9] above, wherein the dielectric green sheet has a thickness of 3 μm or less.
[0153] In addition, the present invention is not limited to the above-mentioned embodiments, and various changes can be made within the scope shown in the technical scheme. The embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. In addition, one or more of the requirements described in the above-mentioned embodiments, etc. are sometimes omitted. That is, it should be noted that if it is a person skilled in the art, it is easy to make various deformations or corrections based on the present invention. In addition, it should be noted that these deformations or corrections are included in the scope of the present disclosure. In addition, as long as the law permits, the contents of Japanese Patent Application No. 2022-110487 as a Japanese patent application and all the documents cited in this specification are cited as part of the record of the text.
[0154] Description of Reference Numerals
[0155] 1: Multilayer ceramic capacitor;
[0156] 10: Ceramic laminate;
[0157] 11: internal electrode layer;
[0158] 12: dielectric layer;
[0159] 20: external electrode;
[0160] 21: external electrode layer;
[0161] 22: Electroplating layer.
Claims
1. A conductive paste comprising conductive metal powder, ceramic powder, binder resin, additives and organic solvent, wherein: The organic solvent comprises (A) and (B), (A) is at least one selected from dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, (B) is at least one selected from ethylene glycol monobutyl ether acetate and dipropylene glycol methyl ether acetate, The additive contains more than 0 mass % and 2.0 mass % or less of the phosphoric acid polyester based on the total amount of the conductive paste.
2. The conductive paste according to claim 1, wherein The conductive metal powder is composed of a metal powder selected from Ni, Pd, Pt, Au, Ag, Cu and alloys thereof.
3. The conductive paste according to claim 1 or 2, wherein: The ceramic powder is barium titanate (BaTiO3) which is a perovskite-type oxide.
4. The conductive paste according to claim 1 or 2, wherein: The ceramic powder is a perovskite-type oxide ferroelectric.
5. The conductive paste according to claim 1, wherein The conductive paste is a conductive paste for an internal electrode layer of a multilayer ceramic device having a dielectric layer and the internal electrode layer formed using a dielectric green sheet, wherein the dielectric ceramic powder contained in the dielectric green sheet and the ceramic powder contained in the conductive paste have the same composition.
6. The conductive paste according to claim 1 or 2, wherein: When the conductive paste is applied to a green sheet containing barium titanate and polyvinyl butyral resin to a wet film thickness of 38 μm and dried at 75° C. for 20 minutes to obtain a dry film, the Vickers hardness measured under the following conditions is 5 Hv or more and 11 Hv or less. (Measurement conditions) The Vickers hardness of the surface of the dried film was measured using a micro Vickers hardness tester under the condition of a test force of 98 mN.
7. A dry film, wherein: The dry film is formed using the conductive paste according to claim 1 or 2.
8. An internal electrode of a multilayer ceramic capacitor, wherein: The internal electrode is formed using the dry film according to claim 7.
9. A multilayer ceramic capacitor, wherein: The multilayer ceramic capacitor comprises the internal electrode according to claim 8 and a dielectric layer formed using a dielectric green sheet.
10. The multilayer ceramic capacitor according to claim 9, wherein The dielectric green sheet has a thickness of 3 μm or less.
Citation Information
Patent Citations
Paste for internal electrodes, method for manufacturing the same, and multilayer ceramic capacitor
JP2017143202A
Ink set and method for inspecting recording head
JP2022110487A